THE TYPES OF EXPLORING LANGUAGE STYLE OF TEACHERS’ AND STUDENTS’ IN THE CLASSROOM INTERACTION (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aims to explore the types of language styles used by teachers in teaching in classroom interaction and to explore the types of language styles used by students in classroom interaction. The research was conducted at SMAN 21 Makassar in BTP, South Sulawesi, Indonesia. This research used a descriptive qualitative method, classroom observation and document review as the instruments for the data collection. The total sample was 35 students. The results showed that four language styles the teacher used in learning process. First the researcher found that the teacher used formal styles 4 times: where the teacher reminded the students about their tasks, gave the topic to discuss, gave an instruction to make arguments, and read the arguments. Second the researcher found that the teacher used consultative style once: where the teacher asked the students about the duration of their joining in this lesson. Third the researcher found that the teacher used casual styles three times, such as the teacher instructed the students to finish the tasks, to open the book, and to discuss it to their friends whether it is difficult. Fourth the researcher found that the teacher used intimate styles three times, such as the teacher divided the students into some groups, asked the students about the due time to submit the task, and used makassarness accent to communicate. Three language styles found by the researcher used by the students in learning process: First the researcher found that the students used formal style once: where one of the students led his classmate to welcome the teacher. Second the researcher found that the students used casual style once: where the students discussed about the material by using makassar accent. Third the researcher found that the students used intimate style: where the student asked his classmate to clarify the teacher’s statements/explanations. In conclusion, the researcher suggests that the teacher must be able to control the classroom when teaching in the classroom. In addition, the teacher gives students opportunity to ask a question and must give special treatment to the students in order to pay attention to the teacher when he explains something. Besides that the interactions in the classroom use several styles of language to support of the teaching and learning process so that it continues to run well.